Single walled carbon nanotubes contain residual iron oxide impurities which can dominate their electrochemical activity - Kruusma, J; Mould, N; Jurkschat, K; Crossley, A; Banks, C (2007)
We demonstrate with the electrochemical oxidation of hydrazine and the electrochemical reduction of hydrogen peroxide that residual iron impurities, likely in the form of Fe3O4, can dominate the electrochemical response of single-walled carbon nanotubes. © 2007 Elsevier B.V. All rights reserved.